War is a force that gives us meaning - Hedges, Chris (Random House, 2003)
"Drawing on the literature of combat, from Homer and Shakespeare to Erich Maria Remarque and Michael Herr, Hedges shows how human beings are conditioned to embrace what he calls "the myth of war"--The idea that combat is noble, selfless, and glorious. And yet if human history is any guide, nations and imperiums have stumbled and even fallen when they believed the myths peddled about war and about themselves. The reality of war, which Hedges knows first-hand, is about the destruction of culture, the perversion of human desire, and the embrace, ultimately, of death over life."--publisher description